Il giovane Lenin : la giovinezza di Lenin raccontata da un compagno di lotta - Trotski, Leon; Maitan, Livio (Verona : Arnaldo Mondadori, 1971)
Fonds Perrone
Italiaans
Monografie
Keywords: Lenin, Vladimir